Electrospinning synthesis of few‐layer hexagonal antimonene nanosheets as anode for lithium‐ion batteries. Issue 4 (30th May 2022) - Sun, Haibin; Zheng, Wenrui; Liu, Congcong; Liang, Shuangshuang; Huang, Mingyue; Li, Ya; Gao, Shasha; Feng, Minghai; Liu, Shenghong; Xie, Wenhe
Abstract: Two‐dimensional (2D) antimonene (Sb) is regarded as a promising anode candidate for lithium‐ion batteries owing to its theoretical capacity (660 mAh g −1 ). Preparing hexagonal Sb nanosheets (H‐SbNs) has been addressed an effective strategy to resolve the drastic volume expansion and the pulverization issues. Here, we present a facile method to prepare the few‐layer H‐SbNs on the surface of carbon fibers via the electrospinning with a thermal annealing process. When evaluated as an anode for lithium storage, the H‐SbN electrode delivers a high rate performance and excellent cycling stability. Electrochemical analysis reveals that the H‐SbN electrode displays the mainly diffusion‐controlled capacitive contributions and excellent lithium‐ion and electron transport. Our findings demonstrate that 2D materials are superior to use as the Sb‐based anodes for electrochemical lithium storage.